Transformasi Perpustakaan Berbasis Inklusi Sosial di Perpustakaan Daerah Kabupaten Purwakarta: Studi Kasus mengenai Lipperpul (Lima Program Perpustakaan Unggulan) - Titis Ardia Meva; Lusiana, Elnovani; Yanto, Andri (UPT Perpustakaan UIN Alauddin Makassar, 2024)
The concept of a library based on social inclusion is an interesting thing to research and understand more deeply. This research aims to explore how Lipperpul (Five Featured Library Programs) in Purwakarta Regency Regional Library presents social inclusion. This research uses a qualitative method with a case study approach. Data collection techniques through participant observation, interviews, documentation, and literature study. This research was conducted on 3 informants of young expert librarians of Purwakarta Regency Regional Library, 1 informant of basic guitar class teacher at Purwakarta Regency Regional Library, and 2 informants of the community who utilize Lipperpul. Data analysis in the study through data reduction, data presentation, and conclusion drawing. The results of this study show social inclusion through Lipperpul: social transformation, empowerment, and lifelong learning. This research is expected to know and understand social inclusion through Lipperpul